A role for fermentation in aerobic conditions as revealed by computational analysis of maize root metabolism during growth by cell elongation - Hunt, Hilary; Leape, Stefan; Sidhu, Jagdeep Singh; Ajmera, Ishan; Lynch, Jonathan P.; Ratcliffe, R. George; Sweetlove, Lee J. (The Plant journal : for cell and molecular biology, 2023)
SUMMARY The root is a well‐studied example of cell specialisation, yet little is known about the metabolism that supports the transport functions and growth of different root cell types. To address this, we used computational modelling to study metabolism in the elongation zone of a maize lateral root. A functional‐structural model captured the cell‐anatomical features of the root and modelled how they changed as the root elongated. From these data, we derived constraints for a flux balance analysis model that predicted metabolic fluxes of the 11 concentric rings of cells in the root. We discovered a distinct metabolic flux pattern in the cortical cell rings, endodermis and pericycle (but absent in the epidermis) that involved a high rate of glycolysis and production of the fermentation end‐products lactate and ethanol. This aerobic fermentation was confirmed experimentally by metabolite analysis. The use of fermentation in the model was not obligatory but was the most efficient way to meet the specific demands for energy, reducing power and carbon skeletons of expanding cells. Cytosolic acidification was avoided in the fermentative mode due to the substantial consumption of protons by lipid synthesis. These results expand our understanding of fermentative metabolism beyond that of hypoxic niches and suggest that fermentation could play an important role in the metabolism of aerobic tissues. Significance Statement Fermentation is usually associated with low oxygen conditions but here we show how fermentation can be important in aerobic tissues. Specifically, the provision of carbon skeletons and energy for expanding cells in the maize root is most efficiently achieved by a high rate of glycolysis facilitated by fermentative production of lactate and ethanol.